The Impact Of Intellectual Capital On Business Performance In Taiwanese Design Industry - Shih, Cheng-Ping; Chen, Wen-Chih; Morrison, Melton (Journal of Knowledge Management Practice, 2010)
Transforming into a knowledge-based economy, there is an increasing need for Taiwan to explore how intellectual capital creates value for companies. This paper presents empirical data in understanding how intellectual capital influences business performance; specifically in the context of Taiwanese design companies. An Intellectual capital questionnaire was adopted to measure the intellectual capital components, including human capital, structural capital, and relational capital. 87 samples are collected and the data are analyzed by Partial Least Squares (PLS) method. The empirical result of PLS shows that intellectual capital does have significant influence on Taiwanese design companies’ performance. However, due to Taiwanese design companies’ organizational structure, structural capital does not support a positive influence on their performance. Also, it is indicated that ‘number of employees in the company’ and the ‘company age’ influence the structural capital on business performance.